Efektivitas Gel Ekstrak Tangkai Talas (Colocasia esculenta L.) untuk Penyembuhan Luka Bakar pada Tikus Putih Jantan - Erni Rustiani; Nisa Najwa; Lulu Nurzillah (JURNAL ILMU KEFARMASIAN INDONESIA, 2022)
The stalk of Colocasia esculenta (L.) plant contains flavonoids and saponins. Flavonoids presented effects in respect of the inflammatory process, re-epithelialization and oxidative stress. Saponin not only promotes re-epithelialization of the wound but also effectively inhibits inflammatory reactions during the early phase, and promotes matrix synthesis throughout the wound healing process. So that the content of metabolites in Colocasia stalks is thought to be able to play a role in the healing process of burns, especially wounds with complications of infection. One of the topical dosage forms to treat burns is a gel dosage form. This study aimed to make and determine the effectiveness of gel of Colocasia stalk extract in healing infected burns in white male rats. The test animals were divided into five groups, each consisting of 5 rats. The groups given the gel were F1 (1% w/w), F2 (3% w/w), F3 (5% w/w). While the positive control group was given (Bioplacenton®) and the negative control group (gel base). The gel was given once a day, and the method used was the Morton method. Observations included evaluation of gel quality, decrease in wound diameter, and epithelialization time. The results showed that gel of Colocasia stalk extract (1%, 3%, and 5% w/w) had a good quality and significantly wound infected burns (p<0.05). The decrease in wound diameter and epithelialization time had a value (p<0.05) compared to the negative control group. The healing effect of burns depends on the concentration of the dried extract of Colocasia stalk in the gel preparation. Extract concentration of 5% w/w (F3) has the most effective percentage of burn wound healing for 13 days.